Structured Illumination Chip Based on Integrated Optics*Supported by the National Natural Science Foundation of China under Grant No 61334008, the National High-Technology Research and Development Program of China under Grant No 2015AA016904, and the Instrument Developing Project of the Chinese Academy of Sciences under Grant No YZ201301. (May 2016) - Liu 刘, Yong 勇; Wang 王, Chen 辰; Nemkova, Anastasia; Hu 胡, Shi-Ming 诗铭; Li 李, Zhi-Yong 智勇; Yu 俞, Yu-De 育德
Abstract : A compact structured illumination chip based on integrated optics is proposed and fabricated on a silicon-on-insulator platform. Based on the simulation of Gaussian beam interference, we adopt a chirped diffraction grating to achieve a specific interference pattern. The experimental results match well with the simulations. The portability and flexibility of the structured illumination chip can be increased greatly through horizontal encapsulation. High levels of integration, compared with the conventional structured illumination approach, make this chip very compact, with a footprint of only around 1 mm 2 . The chip has no optical lenses and can be easily combined with a microfluidic system. These properties would make the chip very suitable for portable 3D scanner and compact super-resolution microscopy applications.